NATURAL ATTENUATION OF AROMATIC HYDROCARBON FROM SANDY SEDIMENT IN BOA VIAGEM BEACH, GUANABARA BAY, RJ, BRAZIL - Fontana, Luiz Francisco; da Silva, Frederico Sobrinho; Krepsky, Natascha; Barcelos, Mabel Araujo; Crapez, Mirian Araujo Carlos (Geochimica Brasiliensis, 2012)